The alpha-1 Adrenoceptor Antagonist Tamsulosin for the Treatment of Voiding Symptoms Improves Nocturia and Sleep Quality in Women - Kim, Sun-Ouck; Choi, Hyang Sik; Kwon, Dongdeuk (Urology Journal, 2014)
Abstract Purpose: Nocturia is the main cause of disturbance of sleep maintenance and negatively impacts quality of life (QoL). We assessed the effects of the ?1-adrenoceptor antagonist, tamsulosin, on nocturia and quality of sleep, for the treatment of lower urinary tract symptoms (LUTS) in women with a maximal flow rate (Qmax) less than 15 mL/sec. Materials and Methods: From January 2008 to December 2009, women with LUTS [Qmax ? 15 mL/s, International Prostate Symptom Score (IPSS) ? 8] and nocturia (void/night ? 1) were selected for this study. Two hundred ninety six patients completed voiding diary, a questionnaire on the Medical Outcomes Study (MOS) sleep scale and underwent follow-up evaluation after 4 weeks of treatment (tamsulosin, 0.2 mg, once daily). Effectiveness was assessed by analysis of the IPSS, the bother score, the Qmax, and postvoid residual urine (PVR). Results: The mean number of voids per night was 2.66 ± 1.3, and the total IPSS and bother scores were 15.2 ± 8.9 and 3.4 ± 1.2, respectively. Clinical parameters, including the IPSS, the bother score, the Qmax and the PVR, improved significantly from baseline after treatment (P < .05). The change in nocturia was -1.12 (P < .05). Concerning sleep quality, the sleep problem index showed a significant decrease. Among the items on the sleep subscale, sleep disturbance, somnolence, and sleep adequacy were significantly changed (P < .05). Conclusion: The ?1-adrenoceptor antagonist tamsulosin significantly improved nocturia and sleep quality as well as LUTS in women with low Qmax.